Method for preparing nanoparticle / polymer total heat exchange membrane with assistance of dispersing agent
The nanoparticle/polymer full heat exchange membrane assisted by dispersing agents is solved, and the problem of gas barrier and moisture permeability in the prior art is not possible, and efficient heat exchange performance is achieved.
Patent Information
- Application Number
- CN202510043333.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While the existing full heat exchange membrane improves gas barrier properties, the moisture permeability performance is degraded and both are not taken into account.
The nanoparticle/polymer full heat exchange membrane is assisted by dispersing agents. During the nanoparticle grafting process, dispersants are used to promote the uniform dispersion of the nanoparticles and hydrophilic oligomers to form a dense surface structure.
High moisture permeability and low gas permeability are achieved, the gas barrier performance is improved by 130%, and the moisture permeability is increased by 31%, avoiding the "trade-off" effect.
Smart Images

Figure CN119431855A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of total heat exchange membranes for fresh air systems, and in particular to a method for preparing a nanoparticle / polymer total heat exchange membrane with the aid of a dispersant. Background Art
[0002] With the improvement of living standards, people's requirements for indoor air quality are constantly increasing. The appropriate oxygen content, temperature and humidity of indoor air determine the indoor air quality. The fresh air system can adjust the temperature and humidity of the air to ensure the comfort of people's lives, but there is a large amount of heat or cold consumption in the process. The energy consumption of the fresh air system accounts for about 20%~40% of the energy consumption of the air conditioning system. The full heat exchanger recovers sensible heat and latent heat through the full heat exchange membrane to reduce the energy consumption of the fresh air system. The full heat exchange membrane determines the heat exchange efficiency of the full heat exchanger. At present, most products on the market use paper membrane as the full heat exchange membrane, which cannot effectively isolate harmful gases and pathogens, causing them to flow back from the exhaust air to the intake air, causing cross contamination, and failing to achieve the purpose of effectively replacing fresh air.
[0003] The polymer heat exchange membrane has aroused a research boom due to its low energy consumption and washable advantages. The research mainly focuses on the compounding of different membrane materials and additives to prepare various heat exchange membranes with excellent moisture permeability, high gas barrier properties, mildew resistance and flame retardancy, so as to replace paper membranes, more effectively reduce air conditioning energy consumption and improve indoor air quality. The latent heat exchange process, which plays a major role in heat exchange, is driven by the water vapor partial pressure difference on both sides of the membrane, and does not require additional energy consumption; the membrane separates the air intake and exhaust to prevent cross contamination; the structure is simple, there are no rotating parts, and the operating cost is low. It is currently the most energy-saving and environmentally friendly way to prepare heat exchange membranes.
[0004] At present, the polymer heat exchange membranes on the market are mainly composed of film-forming components and hydrophilic components. Some manufacturers add nano inorganic particles to pursue high barrier properties against harmful gases. Patent CN105709617A discloses a method for preparing organic-inorganic hybrid heat exchange membranes by sol-gel method. The method is to uniformly mix inorganic precursors and organic polymers in a co-solvent and then sol and gel to obtain an organic-inorganic hybrid membrane. However, it takes too long for the precursor to be hydrolyzed, polycondensed, and uniformly dispersed in an organic solution, and vacuum degassing and other conditions are also required. In addition, the CO2 permeation rate is high and the moisture permeability is poor.
[0005] Patent CN118904117A discloses a method for preparing a PVDF polymer composite membrane for improving the heat exchange efficiency of a total heat exchanger, the preparation method comprising: soaking the support layer in anhydrous ethanol, taking it out and drying it in a blast drying oven to obtain support layer A: fixing support layer A on a clean glass plate, using N-N-dimethylacetamide to wet membrane A to obtain support layer B: coating the surface of support layer B with casting liquid, using an adjustable applicator to scrape the film, and obtaining membrane A of different thicknesses; placing membrane A in deionized water and anhydrous ethanol to solidify, and obtaining membrane B after forming: soaking membrane B in deionized water to obtain membrane C; drying to form a film. However, the agglomeration degree of nanoparticles dispersed in the casting liquid is too high, and the uniformity on the surface of the film is not high. The high coating thickness limits the improvement of the moisture permeability of the hydrophilic nanoparticles. With the help of a dispersant, the nanoparticles can be evenly dispersed in the casting liquid, thereby improving the hydrophilic gas barrier properties of the total heat exchange membrane.
[0006] Inorganic nanoparticles such as montmorillonite, graphene oxide, and silica have a large specific surface area and rich pore structure, and can form a dense surface structure. Doping nanoparticles can effectively improve the gas barrier properties of the film and give the composite film other functional properties. For example, patent CN118718770A discloses a method for preparing a ZIF-8 / polyvinyl alcohol-based full heat exchange membrane. The surface structure is roughened by doping ZIF-8 to obtain good hydrophilic properties, which gives the polyvinyl alcohol-based membrane good antibacterial effect. The composite membrane prepared by doping montmorillonite as a gas barrier material has high gas barrier properties, but the moisture permeability of the membrane is reduced (Xie Yu et al. Preparation and performance study of cross-linked chitosan / montmorillonite composite membrane [J / OL]. China Plastics, 2022, 36(3):58-63.). The use of a single gas barrier material cannot achieve the best moisture permeability and gas barrier effect. After adding montmorillonite and calcium chloride to the polyvinyl alcohol-based membrane (Chang Xian et al. Preparation and performance of polyvinyl alcohol-based high moisture permeability and high barrier ternary mixed matrix full heat exchange membrane [J / OL]. Chemical Industry Progress, 2022, 41(2):911-919.), composite membranes doped with hydrophilic materials and gas barrier materials are still restricted by the "trade-off" effect, and the moisture permeability and gas barrier properties of the obtained composite membranes cannot be achieved at the same time; the oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface of oxidized carbon nanotubes and graphene oxide can give the materials good hydrophilic properties, but the thickness of PVDF composite membranes prepared by phase inversion method is not uniformly controlled and the surface uniformity is poor (ZHANG J, XU Z, MAI W, et al. Improved hydrophilicity, permeability, antifouling and mechanical properties of PVDF composite ultrafiltration membranes tailored by oxidized low-dimensional carbon nanomaterials[J / OL]. Journal of Materials Chemistry A, 2013, 1(9):3101.); while nanoparticles grafted with hydrophilic polymers can take into account both high gas barrier and high moisture permeability. After acid-activated carbon nanotubes are grafted with polyetheramine oligomers, they are doped into a polyimide matrix to prepare a mixed matrix membrane (XIAO Y, LEI X, XUE S, et al. MechanicallyStrong, Thermally Stable Gas Barrier Polyimide Membranes Derived from CarbonNanotube-Based Nanofluids[J / OL].ACS Applied Materials&Interfaces, 2021, 13(47):56530-56543.), the membrane has good hydrophilicity and gas barrier ability, but the activation and grafting of carbon nanotubes is not complete, and the performance improvement is limited. The preparation of polyimide membrane requires nitrogen atmosphere, and the multi-step operation steps are cumbersome. The strong acid used is not conducive to human safety, and irritating gases will be volatilized during the preparation of polyimide membrane. Hydrogen peroxide can replace strong acid to activate the surface of nanoparticles, and no irritating gas escapes. In summary, the field of full heat exchange membranes requires a nanomaterial / polymer composite membrane with simple preparation process, convenient operation, and moisture permeability and gas barrier properties. . Summary of the invention
[0007] In order to solve the problem that the prior art cannot have both gas barrier properties and moisture permeability, the present invention provides a method for preparing a nanoparticle / polymer full heat exchange membrane with the aid of a dispersant, and the prepared full heat exchange membrane has a high moisture permeability and a low gas permeability. The method comprises the following steps:
[0008] Step 1: treating the inorganic nanoparticles with hydrogen peroxide at 30-80°C for 3-6 hours, filtering, washing, and vacuum drying at 60-120°C for 4-8 hours to obtain modified nanoparticle powder, adding a coupling agent, a dispersant, the modified nanoparticles and a hydrophilic oligomer to a methanol solution at 30-80°C, reacting for 4-8 hours, and vacuum drying at 50-120°C for 10 hours to remove the residual solvent to obtain inorganic grafted nanoparticles;
[0009] Step 2: Dissolve the obtained nanoparticles, dispersant and film-forming components in deionized water, ultrasonically obtain a uniformly dispersed casting solution, and apply the casting solution to the On one side of the substrate, the nanoparticle / polymer full heat exchange membrane is obtained after drying.
[0010] The inorganic nanoparticles are one or more of titanium dioxide, carbon nanotubes, zinc oxide, graphene oxide, montmorillonite or silicon dioxide.
[0011] The dispersant is one or more of Tween 80, fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or betaine.
[0012] The hydrophilic oligomer is at least one of polyacrylamide, polythiol, polyacrylic acid, polyetheramine, polyethylene glycol or polyvinyl alcohol.
[0013] The coupling agent is one of KH-650, KH-550, A-1160 or A-1100.
[0014] The film-forming component is at least one of polyurethane, polyamide, sodium alginate, gelatin, chitosan, sodium polyacrylate or polyacrylamide.
[0015] The mass fraction of the dispersant in the casting solution described in step 2 is 0.1% to 5%.
[0016] The mass fraction of the nanoparticles in the casting solution is 0.005-3%.
[0017] The substrate is one of polyvinylidene chloride, polycarbonate, polyamide, polytetrafluoroethylene, polyetheramine or polypropylene.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. The dispersant promotes the nanoparticle grafting process. The nanoparticles are fully grafted with hydrophilic oligomers, and the grafting process is simple. The dispersant is adsorbed around the nanoparticles to form a protective layer, which helps to reduce the agglomeration of the nanoparticles in the film-forming components. With the help of ultrasound, the nanoparticles are evenly dispersed in the film-forming components to form a dense surface structure.
[0020] 2. The gas barrier performance of the prepared full heat exchange membrane reaches 4562L / m 2 ·h·bar, which is 130% higher than that of adding only film-forming components (Comparative Example 1), effectively avoiding cross contamination of air intake and exhaust.
[0021] 3. No irritating gas escapes, and the moisture permeability of the prepared full heat exchange membrane is up to 4953.3g / m 2 ·24h, compared with adding only inorganic fillers (Comparative Example 2), the performance was improved by 31%, suppressing the "trade-off" effect. While adding gas barrier fillers to enhance the barrier performance, it also effectively improved the moisture permeability of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Flow chart of the steps for preparing total heat exchange membranes for modified inorganic nanoparticles.
[0023] Figure 2 This is the surface SEM image of the full heat exchange membrane base membrane.
[0024] Figure 3 This is the SEM picture of Comparative Example 1, in which only the film-forming component is coated on the surface of the base film.
[0025] Figure 4 This is the surface SEM image of the comparative example 2 with the montmorillonite full heat exchange membrane added. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments.
[0027] Example 1
[0028] 1. Treat the nano-silica with hydrogen peroxide at 40°C for 4 hours, filter, wash with deionized water, and vacuum dry at 100°C for 4 hours to obtain the modified nano-silica powder. React the coupling agent, Tween 80, KH650, nano-silica powder and polyethylene glycol in a 50°C methanol solution for 5 hours. After the reaction is completed, vacuum dry at 100°C for 10 hours to remove the residual solvent to obtain polyethylene glycol grafted silica powder.
[0029] 2. Dissolve 0.025g grafted nanopowder, 0.75g sodium dodecylbenzene sulfonate, 3g polyacrylamide, 1g sodium alginate and 0.3g hyaluronic acid in 250ml deionized water, stir at 60℃ for 4h, remove cavitations by ultrasonication to obtain uniformly dispersed casting solution, and apply the casting solution for 3 hours. On one side of the substrate, Example 1 was obtained after drying.
[0030] Example 2
[0031] 1. Treat the nano-silica with hydrogen peroxide at 40°C for 4 hours, filter, wash with deionized water, and vacuum dry at 100°C for 4 hours to obtain the modified nano-silica powder. React the coupling agent, Tween 80, KH650, nano-silica powder and polyetheramine in a 50°C methanol solution for 5 hours. After the reaction is completed, vacuum dry at 100°C for 10 hours to remove the residual solvent to obtain polyetheramine grafted silica powder.
[0032] 2. Dissolve 0.025g grafted nanopowder, 0.75g sodium dodecylbenzene sulfonate, 3g polyacrylamide, 1g sodium alginate and 0.3g hyaluronic acid in 250ml deionized water, stir at 60℃ for 4h, remove cavitations by ultrasonication to obtain uniformly dispersed casting solution, and apply the casting solution for 3 hours. On one side of the substrate, Example 2 was obtained after drying.
[0033] Comparative Example 1
[0034] 3 g polyacrylamide, 1 g sodium alginate and 0.3 g hyaluronic acid were mixed and dissolved in 250 ml deionized water, stirred at 60 °C for 4 h, and ultrasonically removed cavitation to obtain a uniformly dispersed casting solution. The casting solution was scraped and coated for 3 On one side of the substrate, comparative example 1 was obtained after drying.
[0035] Comparative Example 2
[0036] 0.025 g of nano-silicon dioxide, 0.75 g of sodium dodecylbenzene sulfonate, 3 g of polyacrylamide, 1 g of sodium alginate and 0.3 g of hyaluronic acid were mixed and dissolved in 250 ml of deionized water, stirred at 60 °C for 4 h, and the cavitation was removed by ultrasonic to obtain a uniformly dispersed casting solution. The casting solution was scraped and coated for 3 On one side of the substrate, comparative example 2 was obtained after drying.
[0037] Comparative Example 3
[0038] 0.25 g montmorillonite, 0.75 g sodium dodecylbenzene sulfonate, 3 g polyacrylamide, 1 g sodium alginate and 0.3 g hyaluronic acid were mixed and dissolved in 250 ml deionized water, stirred at 60 °C for 4 h, and ultrasonically removed cavitation to obtain a uniformly dispersed casting solution. The casting solution was scraped and coated for 3 On one side of the substrate, comparative example 3 was obtained after drying.
[0039] Table 1 lists the moisture permeability and gas permeability of the examples in the present invention.
[0040] Table 1. Example <![CDATA[Water vapor transmission rate (g / m 2 ·24h)]]> <![CDATA[Gas permeability (L / m 2 ·h·bar)]]> Example 1 4643.4 4562 Example 2 4953.3 4853 Comparative Example 1 4672.3 65433 Comparative Example 2 3381.4 5145 Comparative Example 3 3573.5 7426
[0041] Test conditions:
[0042] Water vapor permeability test: At 23°C and 50% relative humidity, the water vapor permeability of the heat exchange membrane was tested using the "GB / T 1037-2021 Plastic film and sheet water vapor permeability test cup weight gain and weight loss method".
[0043] Gas permeability test: At 23°C, the gas barrier performance of the full heat exchange membrane was tested using "GB / T 1038.1-2022 Test method for gas permeability of plastic films and sheets - Part 1: Differential pressure method".
[0044] The above embodiments and comparative examples show that adding nano inorganic particles can improve the barrier properties of the film, but the moisture permeability will also decrease. The asymmetric total heat exchange membrane prepared by doping inorganic nanoparticles grafted with hydrophilic polymers has a dense surface structure and high barrier properties. At the same time, the membrane has good moisture permeability and has efficient heat exchange performance.
Claims
1. A method for preparing a nanoparticle / polymer total heat exchange membrane assisted by a dispersant, characterized in that: The following steps are involved: Step 1: treating the inorganic nanoparticles with hydrogen peroxide at 30-80°C for 3-6 hours, filtering, washing, and vacuum drying at 60-120°C for 4-8 hours to obtain modified nanoparticle powder, adding a coupling agent, a dispersant, the modified nanoparticles and a hydrophilic oligomer to a methanol solution at 30-80°C, reacting for 4-8 hours, and vacuum drying at 50-120°C for 10 hours to remove the residual solvent to obtain inorganic grafted nanoparticles; Step 2: Dissolve the obtained nanoparticles, dispersant and film-forming components in deionized water, ultrasonically obtain a uniformly dispersed casting solution, and apply the casting solution to the On one side of the substrate, the nanoparticle / polymer full heat exchange membrane is obtained after drying.
2. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The inorganic nanoparticles in step 1 are one or more of titanium dioxide, carbon nanotubes, zinc oxide, graphene oxide, montmorillonite or silicon dioxide.
3. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The dispersant in step 1 and step 2 is one or more of Tween 80, fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate or betaine.
4. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The coupling agent in step 1 is at least one of KH-650, KH-550, A-1160 or A-1100.
5. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The hydrophilic oligomer in step 1 is at least one of polyacrylamide, polythiol, polyacrylic acid, polyetheramine, polyethylene glycol or polyvinyl alcohol.
6. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The film-forming component in the casting solution in step 2 is at least one of polyurethane, polyamide, hyaluronic acid, gelatin, chitin, diatomaceous earth or polyacrylamide.
7. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The mass fraction of the nanoparticles in the casting solution described in step 2 is 0.005-3%.
8. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that The mass fraction of the dispersant in the casting solution described in step 2 is 0.1%~5%.
9. The method for preparing a dispersant-assisted method for preparing a nanoparticle / polymer total heat exchange membrane according to claim 1, characterized in that In step 2, the substrate is one of polyvinylidene chloride, polycarbonate, polyamide, polytetrafluoroethylene, polyetheramine or polypropylene.
Citation Information
Patent Citations
Method for preparing organic-inorganic hybrid total heat exchange membrane through sol-gel method
CN105709617A
Hydrophilic grafted multiwalled carbon nanotube modified polyvinylidene fluoride film and preparation method thereof
CN103785304A
Making method of organic-inorganic hybrid separating membrane
CN104415668A
Method for preparing organic-inorganic hybridized full heat exchange film with coupling agent method
CN105521717A
Graphene oxide-polymer hybridized all-heat exchange membrane and preparation method and application thereof
CN105879706A
Cited By
Cleanable, efficient and environment-friendly total heat exchange membrane and preparation method thereof
CN120383763A